2018
DOI: 10.2166/wst.2018.352
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and operational conditions as regulators of fluid properties in full-scale continuous stirred-tank biogas reactors – implications for rheology-driven power requirements

Abstract: Understanding fluid rheology is important for optimal design and operation of continuous stirred-tank biogas reactors (CSTBRs) and is the basis for power requirement estimates. Conflicting results have been reported regarding the applicability of total solid (TS) and/or total volatile solid (TVS) contents of CSTBR fluids as proxies for rheological properties. Thus, the present study investigates relationships between rheological properties of 12 full-scale CSTBR fluids, their substrate profiles, and major oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…3e, f). The values were lower than reported apparent viscosities for reactor sludge receiving other types of substrate, e.g., food waste and slaughterhouse waste [9,37], indicating a lower power consumption for achieving complete mixing compared to the full-scale processes studied by Björn et al, [9]. The flow curves of the two reactors were similar, showing close to Newtonian behaviour with no or low yield stress (not shown).…”
Section: Viscositymentioning
confidence: 61%
See 2 more Smart Citations
“…3e, f). The values were lower than reported apparent viscosities for reactor sludge receiving other types of substrate, e.g., food waste and slaughterhouse waste [9,37], indicating a lower power consumption for achieving complete mixing compared to the full-scale processes studied by Björn et al, [9]. The flow curves of the two reactors were similar, showing close to Newtonian behaviour with no or low yield stress (not shown).…”
Section: Viscositymentioning
confidence: 61%
“…3 The concentration of extracellular polymeric substances (EPS) and soluble microbial products (SMP) (a-d) and the corresponding apparent viscosities (e, f) for reactors R1 and R2, over time (days). The lowercase letters p and s of the EPS and SMP denote the protein and polysaccharide fractions, respectively, and the apparent viscosity was estimated at a shear rate of e 100/s and f 300/s f activated sludge cannot be used to predict the viscosity of all types of AD sludges [9]. Thus, other parameters should be looked for to predict viscosities for AD of sludges from pulp and paper wastewater treatment.…”
Section: Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is, however, not always straightforward to evaluate, since different authors report different relationships between solids and rheological parameters. Previous research reported by Björn et al (2018) [14] on rheology in biogas reactors digesting a selection of substrates revealed tendencies toward different rheological behaviour of the digester sludge for different substrate types. Furthermore, it was demonstrated that the type of substrates used in AD processes determines the importance of different process parameters for rheology in CSTBRs.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, it was demonstrated that the type of substrates used in AD processes determines the importance of different process parameters for rheology in CSTBRs. For example, application of sewage sludge in AD processes was reported to lead to reactor fluid rheology that correlates well with their total solid (TS) and total volatile solid (TVS) contents, while co-digestion of combinations of organic wastes (e.g., food, slaughterhouse, or agricultural wastes) may result in an establishment of complex fluid behaviours, which cannot be simply associated with the solids content of the sludge [14]. Similarly, Battistoni (1997) [15], who compared the rheology of anaerobic sludges from reactors treating either the organic fraction of municipal solid waste (OFMSW), primary, or mixed sewage sludge, reported varying behaviour, depending on the substrate.…”
Section: Introductionmentioning
confidence: 99%